BRAIN MAGNETIC RESONANCE EVALUATION AND PUBERTAL DEVELOPMENT VARIATIONS AMONG FEMALE ADOLESCENTS - Fonseca, Paula; Seixas, Daniela; Fonseca, Helena; Brandão, Sofia; Fontoura, Manuel (BIRTH AND GROWTH MEDICAL JOURNAL, 2017)
Aim: There is evidence that adolescents with distinct rhythms of pubertal maturation have different psychosocial behaviours. However, a relation between pubertal maturation and the development of the prefrontal cortex and limbic system was not yet established. The aim of this study was to apply brain magnetic resonance imaging to investigate brain development of teenagers with similar age but distinct timing of pubertal maturation. Methods: We compared the hormonal profiles and brain structure and volume using magnetic resonance imaging of two groups of 14 year-old girls, four with an early pubertal development (group 1) and three with an average pubertal development (group 2). Results: The age at onset of puberty was the only biological variable that distinguished the two groups (p = 0,05). There were no differences regarding global brain volume. However, early-maturers showed a tendency for an increased volume of all subcortical structures except for nucleus accumbens. Conclusion: To our knowledge, this is the first work to address the relation of pubertal maturation timing and central nervous system development using brain magnetic resonance imaging. The observed tendency for an increased volume of the subcortical structures may be related to a possible delayed development of the nucleus accumbens in early-maturers, and may explain the increased vulnerability of this group to risk behaviours.